Power System Simulation, Control and Optimization - Domínguez-Navarro, José Antonio; Yusta-Loyo, José María (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue "Power System Simulation, Control and Optimization" offers valuable insights into the most recent research developments in these topics. The analysis, operation, and control of power systems are increasingly complex tasks that require advanced simulation models to analyze and control the effects of transformations concerning electricity grids today: Massive integration of renewable energies, progressive implementation of electric vehicles, development of intelligent networks, and progressive evolution of the applications of artificial intelligence.